Feeding behavior innovation increases foraging efficiency in the Amur falcon but may be a threat to Asian particolored bats. Issue 9 (11th September 2022) - Feng, Lei; Li, Jingjing; Qin, Hexuan; Liu, Yingying; Wu, Hui; Feng, Jiang; Jiang, Tinglei
Abstract: Behavioral innovations are rare and infrequent in the natural world, but they are pivotal for animals to respond to environmental changes. The ecological benefits of these innovations remain unknown, especially in wild populations. Here, two foraging strategies and three eating behaviors of the Amur falcon ( Falco amurensis ) were observed during predation on Asian particolored bats ( Vespertilio sinensis ) across 3 years. We demonstrated that an eating behavioral innovation in F. amurensis increased the foraging efficiency of V. sinensis more than twofold during 3 consecutive years. This showed that changes in feeding behavior by a bird strongly influenced the rate of energy intake. Since predation on bats by falcons mainly occurred during the lactation and post‐lactation of bats, this may have a certain level of negative effect on the bat population. Abstract : In this study, two forage strategies and three eating behaviours in the Amur falcon ( Falco amurensis ) were observed during predation on Asian particoloured bats ( Vespertilio sinensis ) across three years. Moreover, we demonstrated that an eating behaviour innovation in F . amurensis increased foraging efficiency on V . sinensis more than twofold during three consecutive years. However, behaviour innovations in Amur falcon may suppress bat population size.